Shared sorrow, shared costs: cost-effectiveness analysis of the empowerment group therapy approach to treat affective disorders in refugee populations - Strupf, Michael; Hoell, Andreas; Bajbouj, Malek; Böge, Kerem; Wiechers, Maren; Karnouk, Carine; Kamp-Becker, Inge; Banaschewski, Tobias; Meyer-Lindenberg, Andreas; Rapp, Michael; Hasan, Alkomiet; Falkai, Peter; et al. (BJPsych Open, 2023)
BackgroundRefugees and asylum seekers (RAS) in Germany need tailored and resource-oriented mental healthcare interventions.AimsTo evaluate the cost-effectiveness of group psychotherapy for RAS with moderate depressive symptoms.MethodThis is a post hoc cost-effectiveness analysis of Empowerment group psychotherapy that was embedded in a stratified stepped and collaborative care model (SCCM) from the multicentre randomised controlled MEHIRA trial. One hundred and forty-nine participants were randomly assigned to SCCM or treatment as usual (TAU) and underwent Empowerment (i.e. level 3 of the SCCM for adults) or TAU. Effects were measured with the nine-item Patient Health Questionnaire (PHQ-9) and quality adjusted life-years (QALY) post-intervention. Health service and intervention costs were measured. Incremental cost-effectiveness ratios (ICER) were estimated and net monetary benefit (NMB) regressions with 95% confidence intervals were performed. Cost-effectiveness was ascertained for different values of willingness to pay (WTP) using cost-effectiveness acceptability curves for probable scenarios. Trial registration number: NCT03109028 on ClinicalTrials.gov.ResultsHealth service use costs were significantly lower for Empowerment than TAU after 1 year. Intervention costs were on average €409.6. Empowerment led to a significant change in PHQ-9 scores but not QALY. Bootstrapped mean ICER indicated cost-effectiveness according to PHQ-9 and varied considerably for QALY in the base case. NMB for a unit reduction in PHQ-9 score at WTP of €0 was €354.3 (€978.5 to −€269.9). Results were confirmed for different scenarios and varying WTP thresholds.ConclusionsThe Empowerment intervention was cost-effective in refugees with moderate depressive symptoms regarding the clinical outcome and led to a reduction in direct healthcare consumption. Concerning QALYs, there was a lack of confidence that Empowerment differed from TAU.